Analysis of Environmental Data to Support Quantification of Historical Releases from a Former Uranium Processing Facility in Apollo, Pennsylvania. Issue 5 (May 2021) - Mohler, H. Justin; Rood, Arthur S.; Grogan, Helen A.; Caffrey, Emily A.; Till, John E.
Abstract : Abstract: This paper describes how environmental measurement data were used to help quantify the spatial impact and behavior of uranium released to the environment from a uranium manufacturing facility in Apollo, PA. The Apollo facility released enriched uranium to the environment while it operated between 1957 and 1983. Historical monitoring data generated by the site, along with other independent data sources, provided a long-term record documenting the presence and behavior of uranium in the local environment. This record of evidence, together with reconstructed estimates of facility releases, has been used to estimate environmental concentrations during facility operations and potential exposures to members of the public. Historical environmental measurement data were also used to confirm predictions of deposition and concentrations in air. The data are used here to derive atmospheric deposition velocities for the uranium emissions. Based on the spatial pattern of measurements and calculated deposition velocities around the facility, the released material contained larger particles that deposited close to the facility, and the released material remains largely in the surface layers of the soil, indicating limited downward mobility. Evidence of measurable impacts was determined to extend a relatively short distance (<500 m) from the facility. The soil data collected around Apollo are also compared to findings related to uranium mobility at another facility where uranium was released to the environment, and similar behavior was observed at both sites.